SK Channel Modulates Synaptic Plasticity by Tuning CaMKIIα/β Dynamics - Shrestha, Amita; Sultana, Razia; Lee, Charles C.; Ogundele, Olalekan M. (Frontiers in Synaptic Neuroscience, 2019)
N-Methyl-D-Aspartate Receptor 1 (NMDAR)-linked Ca++ current represents a significant percentage of post-synaptic transient that modulates synaptic strength and is pertinent to dendritic spine plasticity. In the hippocampus, Ca++ transient produced by glutamatergic ionotropic neurotransmission facilitates Ca++-Calmodulin-dependent kinase 2 (CaMKII) Thr286 phosphorylation and promote long-term potentiation (LTP) expression. At CA1 post-synaptic densities, Ca++ transients equally activate small conductance (SK2) channel which regulates excitability by suppressing Ca++ movement. Here, we demonstrate that upstream attenuation of GluN1 function in the hippocampus led to a decrease in Thr286 CaMKIIα phosphorylation, and increased SK2 expression. Consistent with the loss of GluN1 function, potentiation of SK channel in wild type hippocampus reduced CaMKIIα expression and abrogate synaptic localization of T286 pCaMKIIα. Our results demonstrate that positive modulation of SK channel at hippocampal synapses likely refine GluN1-linked plasticity by tuning dendritic localization of CaMKIIα.